Depressive Symptoms in Younger Women and Men With Acute Myocardial Infarction: Insights From the VIRGO Study. Issue 4 (April 2015) - Smolderen, Kim G.; Strait, Kelly M.; Dreyer, Rachel P.; D'Onofrio, Gail; Zhou, Shengfan; Lichtman, Judith H.; Geda, Mary; Bueno, Héctor; Beltrame, John; Safdar, Basmah; Krumholz, Harlan M.; Spertus, John A.
Abstract : Background: Depression was recently recognized as a risk factor for adverse medical outcomes in patients with acute myocardial infarction (AMI). The degree to which depression is present among younger patients with an AMI, the patient profile associated with being a young AMI patient with depressive symptoms, and whether relevant sex differences exist are currently unknown. Methods and Results: The Variation in Recovery: Role of Gender on Outcomes of Young AMI Patients (VIRGO) study enrolled 3572 patients with AMI (67.1% women; 2:1 ratio for women to men) between 2008 and 2012 (at 103 hospitals in the United States, 24 in Spain, and 3 in Australia). Information about lifetime history of depression and depressive symptoms experienced over the past 2 weeks (Patient Health Questionnaire; a cutoff score ≥10 was used for depression screening) was collected during index AMI admission. Information on demographics, socioeconomic status, cardiovascular risk, AMI severity, perceived stress (14‐item Perceived Stress Scale), and health status (Seattle Angina Questionnaire, EuroQoL 5D) was obtained through interviews and chart abstraction. Nearly half (48%) of the women reported a lifetime history of depression versus 1 in 4 in men (24%; P <0.0001). At the time of admission for AMI, more women than men experienced depressive symptoms (39% versus 22%, P <0.0001; adjusted odds ratio 1.64; 95% CI 1.36 to 1.98). Patients with more depressive symptoms had higher levels of stress and worse quality of life ( P <0.001). Depressive symptoms were more prevalent among patients with lower socioeconomic profiles (eg, lower education, uninsured) and with more cardiovascular risk factors (eg, diabetes, smoking). Conclusions: A high rate of lifetime history of depression and depressive symptoms at the time of an AMI was observed among younger women compared with men. Depressive symptoms affected those with more vulnerable socioeconomic and clinical profiles.